Alienation as a source of political decomposition of society - Matić, Petar; Stojadinović, Miša (Sociološki pregled, 2022)
There are plenty of challenges brought by modern society. Globalisation, modernisation, transition processes, social conflicts and off-the-charts development of technology have resulted in the world changing at overwhelming rates on a daily basis. In such circumstances, the individual finds himself/herself alienated from society. The aim of this paper is to analyse the complexities of the phenomenon of alienation in political theory, as a significant indicator of the collapse of democratic institutions. Following a detailed analysis of theories that are relevant for understanding political alienation, the paper at the same time presents experiences and perspectives of relevance for comprehending political alienation in the Republic of Serbia.